Briquettes Compost and Liquid Fertilizer Application for Yellow Local Rice Growing on Bamboo Rafts as Floating System - Siti Masreah Bernas; Andi Wijaya; Effendy Parlindungan Sagala; Siti Nurul Aidil Fitri; Adipati Napoleon (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2017)
Growing rice had been done previously by applying crumble compost on the floating raft but part of compost was lost through runoff, so briquettes compost needs to be buried in soil.  The aims of this research were to find out the effects of briquettes compost and liquid fertilizer on rice and soil and plant nutrients content. Briquettes compost and liquid fertilizer were made of water mimosa (Neptunia prostrate Lam.).  Briquettes were applied at rates of (0, 10, 20 and 30) ton ha-1 and liquid used at (0 and 20) ml clump-1.  This experiment used Factorial Randomized Block Design.  Briquette compost was made by mixing compost with starch and the application was by inserted into the soil.  Liquid fertilizer was made from extracted compost and the application was sprayed on plant leaves.  Results showed that the application of Briquette compost (10 ton ha-1) increased (0.34%) P and (1.88%) K plant contents significantly, compared to the control treatment were only (0.09%) for P and (1.38%) for K plant contents.  Combination of briquettes compost (20 ton ha-1) and liquid fertilizer (20 ml clump-1) increased dried weight rice significantly to (4.55 ton ha-1)from (1.58 ton ha-1) for control treatment. Briquettes compost inserted into the soil had increased nutrients P and K absorbed due to more contact between roots and nutrients and produced more rice yield.